Desenvolvimento de um sistema inteligente OCR utilizando visão computacional para leitura de etiquetas de roteador - Xavier, Giovane Taveira de Souza (2022)
This final paper consists of the development of an intelligent OCR system using computer vision to read router labels, to extract information to be inserted into programs that perform router tests. The system uses a Raspberry Pi 4 as the system's processing center, coupled to it is a Logitech C270 webcam, responsible for capturing the images of the labels. The vision system uses OpenCV to process the image so that the OCR algorithm extracts the text from the image, after which the program stores and displays this information on screens simulating the test software.